Effect of parenteral nutrition in oxygen escalation/de-escalation in SARS-CoV-2 infected patients who are pre-intubation: A multicenter, observational study. (December 2021) - Subramanian, Kritika; Solomon, Nadia; Faillace, Robert; Menon, Vidya; Raiszadeh, Farbod; Brandeis, Gary
Summary: Background & aims: SARS-CoV-2 infection includes a variety of gastrointestinal manifestations along with the usual viral symptoms of malaise and myalgias. The objective of this study was to determine if intravenous parenteral nutrition (PN) affected the risk of intubation in SARS-CoV-2 patients who were dependent on non-invasive ventilation. Methods: Retrospective, multicenter case-control study which analyzed oxygen requirements for 1974 adults with SARS-CoV-2, who were admitted to the local public hospital system between March 1 and May 17, 2020. Relevant baseline biomarkers were studied over 5 days. The main outcome was an escalation or de-escalation of oxygen requirements relative to the exposure of PN. Results: 111 patients received PN while on non-invasive ventilation. Patients who received PN had a significantly lower odds (p < 0.001) of oxygen escalation in comparison to their control group counterparts (OR = 0.804, 95% CI 0.720, 0.899) when matched for age, body mass index, Charlson comorbidity index, and gender. Conclusion: Initiating PN in the setting of non-invasive ventilation of SARS-CoV-2 infected patients was significantly associated with a lower odds of oxygen escalation. PN does not independently exacerbate oxygen requirements in SARS-CoV-2 infected pre-intubated patients.